2017
DOI: 10.1186/s11658-017-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

ABCC6 knockdown in HepG2 cells induces a senescent-like cell phenotype

Abstract: BackgroundPseudoxanthoma elasticum (PXE) is characterized by progressive ectopic mineralization of elastic fibers in dermal, ocular and vascular tissues. No effective treatment exists. It is caused by inactivating mutations in the gene encoding for the ATP-binding cassette, sub-family C member 6 transporter (ABCC6), which is mainly expressed in the liver. The ABCC6 substrate (s) and the PXE pathomechanism remain unknown. Recent studies have shown that overexpression of ABCC6 in HEK293 cells results in efflux o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“… 9-13 Only few studies have addressed the role of other ABC transporters and no data have been reported for possible involvement in AML of MRP6 ( ABCC6 ) which has been proven to affect the cell cycle and genes expression. 16 , 17 In this study we investigate the correlation of mRNA levels of some ABC transporters in bone marrow samples obtained from healthy donors and AML patients, at diagnosis and after treatment with a combination of Ara-C and either daunoblastin or idarubicin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9-13 Only few studies have addressed the role of other ABC transporters and no data have been reported for possible involvement in AML of MRP6 ( ABCC6 ) which has been proven to affect the cell cycle and genes expression. 16 , 17 In this study we investigate the correlation of mRNA levels of some ABC transporters in bone marrow samples obtained from healthy donors and AML patients, at diagnosis and after treatment with a combination of Ara-C and either daunoblastin or idarubicin.…”
Section: Discussionmentioning
confidence: 99%
“…15 In order to investigate the possible correlation of ABC transporters expression in AML diagnosis and response to drug treatments we studied mRNA expression levels of ABCC6 gene along with the expression of the well-known ABCB1 , ABCC1 and ABCG2 genes in bone marrow samples from 11 AML patients and from 7 healthy donors. The interest for ABCC6 gene derives from the observation, reported in recent studies, that ABCC6 is involved in the control of the cell cycle 16 and regulates genes involved in the immune response. 17 MRP6 is structurally and functionally poorly characterized; 18-21 mutations in this gene cause the Pseudoxanthoma elasticum, but its function and physiological substrate(s) are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies, aimed at understanding the role of ABCC6 in cells that physiologically express it, have shown that ABCC6 -silenced HepG2 cells showed changes in the cell phenotype as a consequence of a gene expression dysregulation and of the cell cycle alteration, suggesting that this protein could have another role besides promoting the PPi accumulation outside the cell (Miglionico et al, 2014 , 2017 ). In this study, a panel of experiments have been performed to verify whether the ABCC6 is involved in the purinergic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…CD73 is considered a key regulator in some cancer processes such as drug resistance, tumor metastasis, and tumor angiogenesis [12,13], therefore is an excellent candidate for cancer therapy [14][15][16]. In previous studies, we have reported that knockdown of Abcc6 in hepatocarcinoma cancer cells (HepG2), or the inhibition of its activity lead to the downregulation of NT5E gene, which codifies for the CD73 protein [17][18][19]. Taken together, these data suggest a close correlation between ABCC6 and CD73.…”
Section: Introductionmentioning
confidence: 65%